Post-Head Trauma Prophylactic Anticonvulsants - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
The effectiveness and safety of antiepileptic agents in the treatment of acute traumatic head injury were determined at the Institute of Child Health, University College, London, UK, by review of 10 randomized controlled trials involving 2036 patients identified from various databases.